HydroLang: An open-source web-based programming framework for hydrological sciences. (November 2022) - Erazo Ramirez, Carlos; Sermet, Yusuf; Molkenthin, Frank; Demir, Ibrahim
Abstract: This paper introduces HydroLang, an open-source and integrated community-driven computational web framework for hydrology and water resources research and education. HydroLang employs client-side web technologies and standards to carry out various routines aimed at acquiring, managing, transforming, analyzing, and visualizing hydrological datasets. HydroLang consists of four major high-cohesion low-coupling modules: (1) retrieving, manipulating, and transforming raw hydrological data, (2) statistical operations, hydrological analysis, and model creation, (3) generating graphical and tabular data representations, and (4) mapping and geospatial data visualization. To demonstrate the framework's capabilities, portability, and interoperability, two detailed case studies (assessment of lumped models and construction of a rainfall disaggregation model) have been presented. HydroLang's unique modular architecture and open-source nature allow it to be easily tailored into any use case and web framework, and it encourages iterative enhancements with community involvement to establish the comprehensive next-generation hydrological software toolkit. Highlights: Open source web-based programming framework for hydrological research and education. A software toolkit for hydrological data retrieval, analysis, and visualization. Modular architecture and detailed guidelines for simple adoption and extension. Sharing models, data, and case studies for large-scale community participation.